Effect of laser annealing on thermally evaporated CdTe thin films for photovoltaic absorber application - Khan N.A.; Rahman K.S.; Aris K.A.; Ali A.M.; Misran H.; Akhtaruzzaman M.; Tiong S.K.; Amin N. (Elsevier Ltd, 2023)
Annealing; Cadmium telluride; Crystal orientation; Deposition; Hall effect; II-VI semiconductors; Laser beams; Lime; Neodymium compounds; Neodymium lasers; Optical properties; Photovoltaic effects; Solar cells; Stoichiometry; Substrates; Surface roughness; Thermal evaporation; Thin film solar cells; Topography; Vacuum evaporation; X ray diffraction; Yttrium aluminum garnet; CdTe; Compositional stoichiometry; Crystalline properties; Hall effect measurement; Laser annealing; ND : YAG lasers; Soda lime glass substrate; Thermal evaporation technique; Thin films; biofilm; crustal structure; detection method; electrical property; film; fuel cell; instrumentation; laser method; optical property; photovoltaic system; stoichiometry